2002
DOI: 10.1016/s0008-6363(01)00471-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cardiac A1 adenosine receptor overexpression on sarcoplasmic reticulum function

Abstract: A(1) adenosine receptor overexpression is associated with a decreased rate of active Ca(2+) transport into the SR. We hypothesize that changes in SR function may cause a depletion of the SR Ca(2+) pool, which might protect from ischemic injury by delaying the development of cytosolic Ca(2+) overload during ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…After stabilization, hearts were perfused for 10 min (preischemia), and normothermic global ischemia was then produced by interruption of the coronary flow for a period of 20 min in the rat and 12 min in the mouse (ischemia). Although the term ischemia refers to the interruption of blood flow, it is used in the present experiments to refer to the interruption of coronary perfusion of saline solution, consistent with previous reports (5,7,27,41). Previous experiments in the isolated rat heart have shown that a 20-min period of ischemia did not produce irreversible damage (29).…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…After stabilization, hearts were perfused for 10 min (preischemia), and normothermic global ischemia was then produced by interruption of the coronary flow for a period of 20 min in the rat and 12 min in the mouse (ischemia). Although the term ischemia refers to the interruption of blood flow, it is used in the present experiments to refer to the interruption of coronary perfusion of saline solution, consistent with previous reports (5,7,27,41). Previous experiments in the isolated rat heart have shown that a 20-min period of ischemia did not produce irreversible damage (29).…”
Section: Methodssupporting
confidence: 61%
“…These findings indicate that, although both PLB phosphorylation sites are involved in the mechanical recovery after ischemia, Thr 17 appears to play a major role. -ATPase 2 (SERCA2)] and/or in the rate of Ca 2ϩ reuptake by the SR have been described in several species, including rats, mice, dogs and humans, submitted to moderate and reversible injury during cardiac surgery (21,23,41,43). A decrease in the intracellular Ca 2ϩ transient has indeed been described in stunned myocytes isolated from chronically instrumented pigs (18) but was not detected in stunned rat myocytes and ventricular trabeculae or in isolated perfused ferret and dog hearts (5,9,11,18 appears to be normalized before complete recovery of myocardial performance in several species (5, 9, 11) does not necessarily mean that Ca 2ϩ homeostasis is not altered during ischemia and reperfusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, experimental evidence indicates that the function of the SR is altered both in reversible and irreversible ischemiareperfusion injury (30)(31)(32)(33)(34). In particular, in the case of myocardial stunning, a decrease in the activity of SERCA2a and/or in the rate of Ca 2+ reuptake by the SR has been described in several species (31)(32)(33)(34).…”
Section: Stunningmentioning
confidence: 99%
“…In particular, in the case of myocardial stunning, a decrease in the activity of SERCA2a and/or in the rate of Ca 2+ reuptake by the SR has been described in several species (31)(32)(33)(34). Thus, an obvious question is: why does the intracellular Ca 2+ transient remain unaltered in species in which SR function is depressed?…”
Section: Stunningmentioning
confidence: 99%